2020
DOI: 10.2174/1874609813666200711153223
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Regulation of Immune Function: Impact on Numerous Diseases

Abstract: : Melatonin is well known as a neuroendocrine hormone that promotes sleep. However, the many other attributes of melatonin are less apparent and not as widely appreciated. The purpose of this review is to summarize the qualities of melatonin relating to immune function. The relevance of melatonin in partially or wholly restoring optimal function in a series of disorders related to immune dysfunction is addressed. This includes the potential relief of both autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 121 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…It is generally safe to use and is used to treat insomnia, jet lag and various sleep disorders, thrombocytopenia (chemo-induced), ‘winter blues’ and seasonal affective disorder (SAD), and tardive dyskinesia [ 40 , 41 , 42 , 43 ]. Melatonin also has some immune-regulatory and anticancer effects, but these effects need further studies and validation [ 44 , 45 ]. Melatonin is also produced synthetically and is freely available as an OTC dietary supplement.…”
Section: Metabolism Of Trpmentioning
confidence: 99%
“…It is generally safe to use and is used to treat insomnia, jet lag and various sleep disorders, thrombocytopenia (chemo-induced), ‘winter blues’ and seasonal affective disorder (SAD), and tardive dyskinesia [ 40 , 41 , 42 , 43 ]. Melatonin also has some immune-regulatory and anticancer effects, but these effects need further studies and validation [ 44 , 45 ]. Melatonin is also produced synthetically and is freely available as an OTC dietary supplement.…”
Section: Metabolism Of Trpmentioning
confidence: 99%
“…GO analysis clearly showed that the significantly enriched biological process mainly included the immune process in the mice treated with melatonin. Many studies have shown that melatonin has a positive effect on immunity [ 16 ]. In the IPA analysis of canonical pathways, we found that the most activated pathways affected by melatonin treatment prior to radiation included LPS/IL-1-mediated inhibition of RXR function and Toll-like receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent low grade inflammation is thought to underlie most unresolved chronic disease states like diabetes, Alzheimer's disease, and cardiovascular diseases. 2,3 A chronic inflammatory state is also associated with normal aging and may contribute several of the hallmarks of senescence. 4 The causal basis of both acute and chronic inflammation appears to be largely by way of identical pathways, involving the same transcription factors like IFN regulatory factor 5 (IRF5) 5 and NF-kB, and kinases such as Akt.…”
Section: Impact Statementmentioning
confidence: 99%
“…Melatonin is a natural product of widespread occurrence in plants and animals which acts on immune function, both by inhibiting acute non-selective inflammation and by enhancing a desired immune response. 2 Melatonin can effect upregulation of SIRT-1 which leads to inhibition of pro-inflammatory NF-kB. 65 It has been proposed as a potential adjuvant in the treatment of SARS-CoV-2.…”
Section: Melatoninmentioning
confidence: 99%
See 1 more Smart Citation